Integrasi Kurikulum Cambridge dan Kurikulum Nasional dalam Pengembangan Pendidikan Islam (Kajian Teoretis) - Sholikha, Riadhotus; Arif Syihabuddin, Muhammad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The process of globalization and the internationalization of education have raised academic concerns regarding the potential erosion of Islamic and national values in the implementation of international curricula within Islamic schools. This condition necessitates a curriculum integration model capable of harmonizing global academic standards with the fundamental objectives of Islamic education. This article aims to analyze theoretically the integration of the Cambridge Curriculum and the National Curriculum as a strategic approach to the development of Islamic education. This study employs a library research method with a qualitative descriptive-analytical approach through the examination of books, scholarly journal articles, and relevant educational policy documents. The findings indicate that the Cambridge Curriculum excels in fostering critical thinking, twenty-first-century skills, and global competencies, while the National Curriculum plays a significant role in strengthening national values and character education. The integration of both curricula enables the development of Islamic education that balances academic excellence, Qur’anic character formation, and global readiness among students. The study implies that curriculum integration should be conceptually well-designed, supported by teachers’ pedagogical competence, and reinforced by value-oriented educational policies to ensure that Islamic education remains relevant and globally competitive without losing its Islamic identity